Excessive Private Sector Leverage and Its Drivers : Evidence from Advanced Economies - Jarmuzek, Mariusz (IMF Working Papers; Working Paper ;, 2017)
Nonfinancial private sector debt increased significantly in advanced economies prior to the global financial crisis and, with a few exceptions, deleveraging has been limited. Furthermore, in some countries households and corporations have continued to accumulate debt. Drawing on the literature, the paper aims to provide a quantitative assessment of the gaps between actual and sustainable levels of debt and to identify the key factors that drive excessive borrowing. Results suggest that variables that are typically found important in studies focusing on borrowing decisions, are also relevant for explaining the debt sustainability gaps.